(untitled) (Web of Teachers: Inderscience Research, 2025)
The article presents the views and opinions of linguists on the approach to the concept of discourse in social advertising and its theoretical aspects. It is also suggested that social advertising discourse is an additional type of advertising discourse that combines similar and different features. The distinguishing feature of advertising discourse is the purpose of the recipient of advertising information, the place of advertising, expressiveness and similar features.